Post-mastectomy Radiotherapy in T1-2 Breast Cancer Patients With One to Three Lymph Node Metastases: A Propensity Score Matching Analysis - Chen, Maoshan; Huang, Yunhui; Leng, Zhengwei; Yang, Guanglun; Li, Fangfang; Yang, Hongwei; Hou, Lingmi (Frontiers in Oncology, 2020)
Introduction: Whether post-mastectomy radiotherapy (PMRT) could improve prognosis for T1-2 breast cancer patients with one to three lymph node metastasis remains controversial. The present study aimed to determine significance of PMRT in patients with T1-2N1M0 breast cancer. Methods: Data of 45,646 patients from the SEER database were analyzed. 12,585 matched patients were included into post-mastectomy radiotherapy group (PMRT) and non-radiotherapy group (no-PMRT), respectively, using propensity score matching method. Univariate and multivariate analyses were performed to determine the prognostic factors of breast cancer, and subgroup analysis was performed according to the number of lymph node metastasis. Results: With the median follow-up of 62 months, 5-year cancer specific survival was 91.48% in PMRT group and 91.88% in no-PMRT group (P=0.405). PMRT did not improve the BCSS in patients with stage T1-2N1M0 (HR=0.99, 95%CI=0.92-1.06, P=0.715). In subgroup analysis, radiotherapy improved the BCSS in three nodes positive patients with the 5-year BCSS was 88.5% in radiation group and 86.6% in no-radiation group (HR=0.78, 95%CI=0.65-0.90, P<0.001). In two nodes positive patients, 5-year BCSS were 90.3% in PMRT group and 89.5% in no-PMRT group, no significant difference between two group (HR=0.96, 95%CI=0.85-1.09, P=0.552). In one node positive patients, 5-year BCSS was higher in no-PMRT group (92.1%) than that in PMRT group (90.8%), radiotherapy increased the cancer related death compared with those who didn’t received (HR=1.21, 95%CI=1.08-1.36, P=0.002). Conclusion: The benefit of PMRT in T1-2N1M0 patients was obviously different, and the recommendation of PMRT for this population should be individualized. Strongly recommend PMRT to three nodes positive patients. PMRT should be suggested cautiously in two nodes positive patient and could be omitted in one node positive patient.